2011
DOI: 10.1002/adma.201103107
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Optimization of a Molecular Glass Photoresist System for Electron Beam Lithography

Abstract: Electron beam lithography is a powerful technique for the production of nanostructures but pattern quality depends on numerous interacting process variables. Orthogonal gradients of resist composition, baking temperatures, and development time as well as dose variations inside writing fields are used to prepare ternary combinatorial libraries for an efficient stepwise optimization of a molecular glass negative tone resist system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…2 However, it has already been shown that some compounds can readily form glassy states under ambient conditions without such treatments, if they present some of the following ''typical'' features: a globular and irregular shape, a poor packing, a structure with few elements of symmetry, the capability to adopt multiple conformations, and the formation of weak and non-specific interactions with neighboring molecules. 3,4 These compounds, called molecular glasses or amorphous molecular materials, are used for various applications ranging from opto-electronics [5][6][7] to nanolithography, [8][9][10] nanopatterning, and amorphous drug formulations. [11][12][13][14] Unlike polymers, small molecules offer the advantages of being easier to purify, characterize and process, which are counterbalanced by their higher (often undesirable) propensity to crystallize upon heating or prolonged standing.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, it has already been shown that some compounds can readily form glassy states under ambient conditions without such treatments, if they present some of the following ''typical'' features: a globular and irregular shape, a poor packing, a structure with few elements of symmetry, the capability to adopt multiple conformations, and the formation of weak and non-specific interactions with neighboring molecules. 3,4 These compounds, called molecular glasses or amorphous molecular materials, are used for various applications ranging from opto-electronics [5][6][7] to nanolithography, [8][9][10] nanopatterning, and amorphous drug formulations. [11][12][13][14] Unlike polymers, small molecules offer the advantages of being easier to purify, characterize and process, which are counterbalanced by their higher (often undesirable) propensity to crystallize upon heating or prolonged standing.…”
Section: Introductionmentioning
confidence: 99%
“…The tailored star block copolymers were synthesized utilizing the core‐first ATRP route by the full conversion of a first monomer and in situ polymerization of additional added monomer, resulting in narrow polydispersity (polydispersity index (PDI) < 1.2). Their application for lithographic patterning was efficiently optimized by a combinatorial investigation25 and the new high‐performance star resist material features an impressive improvement in sensitivity and solubility, in contrast to randomly distributed star polymers or a reference linear terpolymer.…”
Section: Methodsmentioning
confidence: 99%
“…Recently we have identified a synergistic effect for post exposure bake and resist composition. Therefore the composition gradient was applied perpendicular to the temperature gradient of post exposure bake and combined with an exposure dose gradient as a ternary gradient [ 23 , 24 , 25 ]. These different gradient preparation techniques for organic thin film investigations demonstrate impressively the fast and effective variable investigation in one experiment.…”
Section: Introductionmentioning
confidence: 99%